The Critical Role of Data Engineering in Modern Claims Adjudication - Pavan Kumar Boyapati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Data engineering serves as the cornerstone of modern healthcare claims adjudication, transforming error-prone manual workflows into streamlined, efficient systems with direct impact on patient care and financial outcomes. This technical article explores how innovations in data integration, validation, workflow automation, and advanced analytics are revolutionizing claims processing across the healthcare industry. From microservice architectures and event-driven processing to machine learning algorithms for fraud detection and patient-facing transparency systems, data engineering enables healthcare organizations to process claims with greater speed, accuracy, and cost-effectiveness. The integration of standardized data formats like HL7 FHIR alongside sophisticated knowledge graph implementations creates unprecedented opportunities for semantic interoperability while accommodating complex business rules. These technological advances collectively enhance every stage of the claims lifecycle, from initial submission through adjudication to final payment, ultimately improving healthcare delivery through more efficient financial infrastructure.